2007
DOI: 10.1007/s00445-006-0111-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple origins of obsidian pyroclasts and implications for changes in the dynamics of the 1300 B.P. eruption of Newberry Volcano, USA

Abstract: The pyroclastic deposits of the 1300 B.P. eruption of Newberry Volcano, OR, USA, contain minor amounts of obsidian (1-6 wt.%). The volatile (H 2 O and CO 2 ) contents and textures of these clasts vary considerably. FTIR measurements of H 2 O in obsidian pyroclasts range from 0.1 to 1.5 wt.% indicating equilibration pressures ≤20 MPa. CO 2 contents are low (<10 ppm) except in clasts that also contain xenolith powder that provided a local CO 2 source. Obsidian clasts exhibit a range of color and textural types t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 49 publications
(79 reference statements)
4
39
0
Order By: Relevance
“…We have shown that degassing occurs through fracturing in rhyolitic melts, supporting suggestions that repeated fracturing and healing (RFH) assists degassing, suppressing vesiculation and favoring obsidian formation (Gonnermann and Manga, 2005;Rust and Cashman, 2007;Rust et al, 2004;Tuffen et al 2010).…”
Section: Autobrecciation and Melt Degassing: Obsidian Formationsupporting
confidence: 76%
“…We have shown that degassing occurs through fracturing in rhyolitic melts, supporting suggestions that repeated fracturing and healing (RFH) assists degassing, suppressing vesiculation and favoring obsidian formation (Gonnermann and Manga, 2005;Rust and Cashman, 2007;Rust et al, 2004;Tuffen et al 2010).…”
Section: Autobrecciation and Melt Degassing: Obsidian Formationsupporting
confidence: 76%
“…Fracturing enhances further release of gas (e.g., Castro et al, 2012) and gas-filled cracks connected to the periphery of the system favor the arrest of magma at depth (Tuffen et al, 2003) and its "viscous death" (Pistone et al, 2013). Further potential explosions of gas-poor stagnant magmas may be driven by influx of new volatile-rich magma (e.g., Rust and Cashman, 2007). Outgassing will lead to a more effusive eruption since a large part of the magmatic overpressure will be released.…”
Section: Insights Into Natural Systemsmentioning
confidence: 99%
“…Integrated over time, these cycles permit outgassing and magma densification (Rust et al, 2004;Rust and Cashman, 2007;Cabrera et al, 2011;Castro et al, 2012), potentially assisted by viscous foam collapse and compaction (e.g., Stasiuk et al, 1996). The efficiency of vein-driven outgassing depends on the spatial extent of veins, the timescale over which their permeability is sustained, and the permeability of intercepted magma (Castro et al, 2012;Berlo et al, 2013;Heap et al, 2015).…”
Section: Scientific and Geological Context Tuffisite Veinsmentioning
confidence: 99%